2012
DOI: 10.1176/appi.ajp.2011.11071121
|View full text |Cite
|
Sign up to set email alerts
|

Naltrexone Implant for the Treatment of Polydrug Dependence: A Randomized Controlled Trial

Abstract: Naltrexone implants resulted in higher retention in the study, decreased heroin and amphetamine use, and improved clinical condition for patients, thus providing the first evidence of an effective pharmacological treatment for this type of polydrug dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 22 publications
2
97
0
Order By: Relevance
“…Taken together, this study provides support for the notion that NTX may be useful for the treatment of MA dependence, thus extending upon positive trials for stimulant dependence (Jayaram-Lindstrom et al, 2008a) and polydrug dependence (Tiihonen et al, 2012). Although no clinical trials to date have tested NTX for the treatment of MA dependence, with the exception of a small combination study (Grant et al, 2010), the present work suggests that such trials may be warranted.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Taken together, this study provides support for the notion that NTX may be useful for the treatment of MA dependence, thus extending upon positive trials for stimulant dependence (Jayaram-Lindstrom et al, 2008a) and polydrug dependence (Tiihonen et al, 2012). Although no clinical trials to date have tested NTX for the treatment of MA dependence, with the exception of a small combination study (Grant et al, 2010), the present work suggests that such trials may be warranted.…”
Section: Discussionsupporting
confidence: 71%
“…A clinical trial of a NTX depot implant demonstrated significant benefit over placebo on measures of treatment retention, drug-free urines, and global assessments of functioning in a hard-totreat sample of heroin and amphetamine polydrugdependent individuals (Tiihonen et al, 2012). Further, a recent behavioral pharmacology study found that acute oral NTX significantly reduced craving during cocaine administration in a sample of non-treatment-seeking cocaine users (n = 12) (Comer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It also improved the global clinical condition of the patients. This study suggested naltrexone use as an option for treating polydrug dependence with psychostimulant drugs (Tiihonen et al, 2012). However, in other studies, no beneficial effects of naltrexone were reported in cocaine-and alcoholdependent outpatients when combined with psychotherapy or drug counseling (Schmitz, Stotts, Sayre, DeLaune, & Grabowski, 2004).…”
Section: Naltrexonementioning
confidence: 64%
“…A common concern with treatments that target a specific class of drugs (e.g., methadone for opioid abuse) is that individuals will switch to other drugs of abuse such as amphetamines (Tiihonen, et al, 2012). CocH vector treatment would be vulnerable to this issue.…”
Section: Discussionmentioning
confidence: 99%